Tác động bất đối xứng của chất lượng thể chế đến tạo thanh khoản của ngân hàng: Bằng chứng thực nghiệm từ các nền kinh tế mới nổi đang phát triển châu Á - Nguyễn Kim , Chi; Võ Xuân, Vinh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the asymmetric impact of institutional quality on banks' liquidity creation in emerging Asian countries. Using a panel quantile regression model with unbalanced data for 15 countries over the period 2010–2023, the results indicate that the relationship between institutional quality and liquidity creation is asymmetric. Specifically, institutional quality has a negative impact at lower quantiles but turns positive and statistically significant at higher quantiles. To test the robustness of the results, the study uses alternative measures of both institutional quality and liquidity creation. The consistency of the results confirms the reliability of the conclusions. The analysis of differences between quantiles further clarifies the nonlinearity in the relationship between institutional quality and liquidity creation. The research results imply that when developing and implementing institutional reform policies, policymakers in emerging countries need to carefully consider the characteristics and adaptability of each banking group, especially in the context of an unevenly developed financial system.